Derecho o deber del juez nacional de plantear la cuestión prejudicial ante el Tribunal de Justicia de la Unión Europea (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2017)
This article tries to find out, analyzing the European Union law and the case-law of the European Court of Justice, whether the question referred for a preliminary ruling is a duty and not a right of the national courts. After analyzing this issue, the article focuses on the Spanish case, studing the positioning of the Supreme Court and the Constitutional Court on this and its consequences.
Keywords: Preliminary ruling; rights; duty; case law